Fine-mapping classical HLA variation associated with durable host control of HIV-1 infection in African Americans - McLaren, Paul J.; Ripke, Stephan; Pelak, Kimberly; Weintrob, Amy C.; Patsopoulos, Nikolaos A.; Jia, Xiaoming; Erlich, Rachel L.; Lennon, Niall J.; Kadie, Carl; Heckerman, David; Gupta, Namrata; Haas, David W.; et al. (Human Molecular Genetics, 2012)
A small proportion of human immunodeficiency virus-1 (HIV-1) infected individuals, termed HIV-1 controllers, suppress viral replication to very low levels in the absence of therapy. Genetic investigations of this phenotype have strongly implicated variation in the class I major histocompatibility complex (MHC) region as key to HIV-1 control. We collected sequence-based classical class I HLA genotypes at 4-digit resolution in HIV-1-infected African American controllers and progressors (n = 1107), and tested them for association with host control using genome-wide single nucleotide polymorphism data to account for population structure. Several classical alleles at HLA-B were associated with host control, including B*57:03 [odds ratio (OR) = 5.1; P= 3.4 × 10–18] and B*81:01 (OR = 4.8; P= 1.3 × 10−9). Analysis of variable amino acid positions demonstrates that HLA-B position 97 is the most significant association with host control in African Americans (omnibus P = 1.2 × 10−21) and explains the signal of several HLA-B alleles, including B*57:03. Within HLA-B, we also identified independent effects at position 116 (omnibus P= 2.8 × 10−15) in the canonical F pocket, position 63 in the B pocket (P= 1.5 × 10−3) and the non-pocket position 245 (P= 8.8 × 10−10), which is thought to influence CD8-binding kinetics. Adjusting for these HLA-B effects, there is evidence for residual association in the MHC region. These results underscore the key role of HLA-B in affecting HIV-1 replication, likely through the molecular interaction between HLA-B and viral peptides presented by infected cells, and suggest that sites outside the peptide-binding pocket also influence HIV-1 control.